A remarkable new species of cavernicolous Collartidini from Madagascar (Hemiptera: Heteroptera: Reduviidae) - Chłond, Dominik; Guilbert, Eric; Faille, Arnaud; Baňař, Petr; Davranoglou, Leonidas-Romanos (Zootaxa, 2018)
Mangabea troglodytes sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae) is described based on four specimens collected in a cave of the Namoroka Karstic System, Madagascar, and deposited in the Collection of the Muséum National d’Histoire Naturelle, Paris. The dorsal habitus as well as diagnostic characters of male and female genitalia are extensively illustrated and imaged. A key to species of the genus Mangabea Villiers, 1970 is provided and the degree of cave specialization of the new species is discussed.